ASAS ITIKAD BAIK DALAM MEMORANDUM OF UNDERSTANDING: TINJAUAN TERHADAP HUKUM PERJANJIAN DI INDONESIA - Prima, Muzdalifah Karsa; Sulistyaningrum, Helena Primadianti (Fakultas Hukum Universitas Sriwijaya, 2025)
This research aims to provide in-depth insight into the role of the principle of good faith in Memorandums of Understanding (MoU) in Indonesia and how this principle supports fair and sustainable relations between the parties. The principle of good faith is the legal principle that underlies the formation, implementation and cancellation of agreements, including MoUs. In the context of the MoU, the principle of good faith provides an ethical and legal basis that must be adhered to by the parties involved. This research explains how the principle of good faith influences the process of forming an MoU by emphasizing the importance of transparency, good intentions and mutual understanding between the parties. Apart from that, the principle of good faith also plays an important role in ensuring parties comply with their commitments in accordance with the objectives of the agreement. Within the framework of contract law in Indonesia, this study explains the relevance of the principle of good faith to applicable regulations. Thus, this journal provides an understanding of contract law in Indonesia and the principles underlying it.